Decision Support System Determining the Best Private Universities Using the Analytical Hierarchy Process Method (Case Study: LLDIKTI Wilayah I) - Dewi Wahyuni; M. Rhifky Wayahdi (Sean Institute, 2021)
Private Universities (PTS) are an option to continue post-graduate education, especially in the city of Medan. Quality private universities are very influential in carrying out education. In order to be easy to compete in the wrong world of work such as accepting new workers and especially in increasing career paths, PTS accreditation is very influential in the world of work as one of the requirements for evaluating job application administration files because a good PTS must have good accreditation. Determining PTS in this Medan city is not easy, because there are many PTS in this Medan city. There are too many private universities in existence, making it difficult to choose PTS manually, and the results of the selection are sometimes inaccurate and become a problem in selecting the best PTS. Decision Support System (DSS) is a system that can assist a person in making accurate and targeted decisions. The method used in this Decision Support System uses the Analytical Hierarchy Process (AHP). This method was chosen as one of the best alternatives because it is able to find and select which are the best private universities based on the specified criteria.